WOS research & publications - Nizar, Nurhuda (UiTM, 2023)
This section of the bulletin highlights FBM’s research performance and scholarly output for January–June 2023. It features an extensive list of publications indexed in Web of Science (WoS) covering diverse research areas including sustainable energy, environmental policy, entrepreneurship, Islamic finance, marketing, education, and technology adoption. The compilation showcases contributions from FBM researchers across multiple disciplines, reflecting the faculty’s active involvement in high-impact research and its commitment to strengthening academic visibility and scholarly excellence.